2009
DOI: 10.3852/08-217
|View full text |Cite
|
Sign up to set email alerts
|

A novel Asian clade within the Fusarium graminearum species complex includes a newly discovered cereal head blight pathogen from the Russian Far East

Abstract: We investigated Fusarium graminearum complex (Fg complex) species diversity and toxin potential in European and Asian regions of the Russian Federation and adjoining regions northwest to Finland and south near Harbin, Heilongjiang Province, China, to expand our knowledge of the host range and geographic distribution of these economically devastating cereal head blight pathogens. Results of a recently described multilocus genotyping (MLGT) assay revealed that F. graminearum was the sole Fg complex pathogen in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(147 citation statements)
references
References 31 publications
9
127
0
7
Order By: Relevance
“…The present work is the first study of FGSC species diversity in Norway. All FGSC isolates collected from Norwegian cereals were identified as F. graminearum, which is consistent with previous evidence that F. graminearum is the dominant species within this species complex in Europe (Laday et al 2004;O'Donnell et al 2004;Toth et al 2005;Yli-Mattila et al 2009;Talas et al 2011;Boutigny et al 2014). F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The present work is the first study of FGSC species diversity in Norway. All FGSC isolates collected from Norwegian cereals were identified as F. graminearum, which is consistent with previous evidence that F. graminearum is the dominant species within this species complex in Europe (Laday et al 2004;O'Donnell et al 2004;Toth et al 2005;Yli-Mattila et al 2009;Talas et al 2011;Boutigny et al 2014). F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014).…”
Section: Discussionsupporting
confidence: 74%
“…The isolates of Finnish and Russian origin were sent to us from Tapani Yli-Matila, University of Turku, Finland. Details about the Finish, Russian and German isolates were previously published (Carter et al 2002;Yli-Mattila et al 2009). More details regarding the isolate collections are presented in Table 1.…”
Section: Isolate Collectionmentioning
confidence: 99%
See 3 more Smart Citations